NATURALNESS, WILD-ANIMAL SUFFERING, AND PALMER ON LAISSEZ-FAIRE - HETTINGER, NED (Les ateliers de l'éthique / The Ethics Forum, 2018)
This essay explores the tension between concern for the suffering of wild animals and concern about massive human influence on nature. It examines Clare Palmer’s animal ethics and its attempt to balance a commitment to the laissez-faire policy of nonintervention in nature with our obligations to animals. The paper contrasts her approach with an alternative defence of this laissez-faire intuition based on a significant and increasingly important environmental value: Respect for an Independent Nature (RIN). The paper articulates and defends naturalness value and explores its implications for the laissez-faire intuition and for concern about wild-animal suffering.